KAJIAN METODE ELIMINATION ET CHOIX TRADUISANT LA REALITE SEBAGAI PENDUKUNG DALAM PENGAMBILAN KEPUTUSAN - Ricky, Ricky; Nababan, Esther Sorta Mauli; Suyanto, Suyanto; Herianto, Tulus Joseph (MES: Journal of Mathematics Education and Science, 2024)
The aim of this research is to conduct a study of the ELECTRE method as a support in decision making to obtain the best decision alternative from a number of decision alternatives. This research also aims to determine which bank alternative is the best alternative for stock investment using the ELECTRE method. The data used is secondary data obtained from bank financial reports for 2023 which is an alternative. The alternative banks used consist of 4 large banks in Indonesia. Meanwhile, the criteria used consist of 5 financial ratios, namely Return on Assets, Return on Equity, Price to Book Value, Price to Earning Ratio, and Debt to Equity Ratio. The results of this research show that BBNI shares are the best alternative bank for stock investment. The conclusion that can be obtained is that the ELECTRE method is effective for use as a support in decision making because the decision alternative that will be obtained is the best decision alternative that has a level of suitability above the suitability threshold and also at the same time has a level of nonconformity below the nonconformity threshold.